Persepsi Pekebun Kelapa Sawit Terkait Faktor-Faktor Yang Mendukung Keberhasilan Indonesian Sustainable Palm Oil (ISPO) di Desa Kertabumi: Perceptions of Independent Smallholder Oil Palm Farmers Regarding Factors Supporting the Success of Indonesian Sustainable Palm Oil (ISPO) in Kertabumi Village - Muhamad Yazid Bustomi; Andi Lelanovita Sardianti; Andi Lisnawati; Zainal Abidin; Pandhu Rochman Suosa Putra (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2026)
The implementation of the Indonesian Sustainable Palm Oil (ISPO) certification among smallholder oil palm farmers is a crucial step toward achieving sustainable oil palm plantation management. This study aims to analyze smallholders’ perceptions regarding the factors supporting the successful implementation of ISPO. The method used is a descriptive approach, analyzing the level of importance of each factor based on respondents’ assessments. The sample size consisted of 45 respondents selected through purposive sampling, specifically members of the Bumi Subur Farmers’ Cooperative who are in the process of implementing ISPO. The results indicate that land legality is the most dominant factor and a key aspect in the success of ISPO implementation. Other primary supporting factors include government assistance and the presence of supporting institutions or partners, indicating that external support plays a crucial role in enhancing the capacity of smallholder farmers. Furthermore, factors such as the proper application of standard operating procedures (SOPs) for cultivation and the use of high-quality oil palm seedlings also fall into the “important” category in supporting ISPO success. Meanwhile, factors such as increased productivity, environmentally friendly cultivation practices, availability of production facilities, cultivation experience, and participation in ISPO training fall into the “moderately supportive” category. Factors with relatively lower influence include fresh fruit bunches (FFB) directly purchased by palm oil mills and the reduction of social issues.